2014
DOI: 10.1094/phyto-11-13-0309-r
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity, Reassortment, and Recombination inAlfalfa mosaic virusPopulation in Spain

Abstract: The variability and genetic structure of Alfalfa mosaic virus (AMV) in Spain was evaluated through the molecular characterization of 60 isolates collected from different hosts and different geographic areas. Analysis of nucleotide sequences in four coding regions--P1, P2, movement protein (MP), and coat protein (CP)--revealed a low genetic diversity and different restrictions to variation operating on each coding region. Phylogenetic analysis of Spanish isolates along with previously reported AMV sequences sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 56 publications
4
15
0
Order By: Relevance
“…It has been shown that selection against heterologous gen combinations increases as host colonization progresses along the infection cycle of Cucumber mosaic virus [32], affecting the frequency of genetic exchange. This explains that recombinants and reassortants are often found at low frequencies [33,34], although the frequency of particular combinations may be dependent on agro-ecological factors [17,19], and support the hypothesis of co-adaptation of gene complexes within the viral genomes [32,35].…”
Section: Generation and Modulation Of Genetic Diversity: Driving Forcsupporting
confidence: 67%
See 1 more Smart Citation
“…It has been shown that selection against heterologous gen combinations increases as host colonization progresses along the infection cycle of Cucumber mosaic virus [32], affecting the frequency of genetic exchange. This explains that recombinants and reassortants are often found at low frequencies [33,34], although the frequency of particular combinations may be dependent on agro-ecological factors [17,19], and support the hypothesis of co-adaptation of gene complexes within the viral genomes [32,35].…”
Section: Generation and Modulation Of Genetic Diversity: Driving Forcsupporting
confidence: 67%
“…Analysis of their sequences indicates that both mechanisms contribute significantly to the generation of variability in the evolution and diversification of certain taxonomic groups [11][12][13][14][15][16]. Recombination and reassortment events may involve members of the same plant virus species [17][18][19], members of different species [20][21][22][23][24] or even genus [25]. Genetic exchange by recombination or reassortment may have important epidemiological implications of practical relevance, even more than mutation, as it has been associated to host jumps, host range expansion, changes in virulence, breaking of host resistance and finally, the emergence of new viral plant diseases.…”
Section: Generation and Modulation Of Genetic Diversity: Driving Forcmentioning
confidence: 99%
“…It provides evidence for two distinct PNRSV phylo-groupings for each of RNA1 and RNA2, which were observed for similar gene regions of RNA1 and RNA2 of the Bromoviridae family members Alfalfa mosaic virus (AMV) and Cucumber mosaic virus (CMV; genus Cucumovirus ) [52, 53]. Phylogenetic analysis of CP sequence variants from the 53 plant samples diverged into the three already defined PNRSV RNA3 phylo-groups [26, 27, 30, 32], even though a smaller portion of the genome was used.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Bergua et al. () showed that agroecological factors including the reassortant one are involved in survival and in their geographical distribution of AMV genetic types. To date, new genetic type IIB is exclusively composed of several Spanish isolates and two isolates from New Zealand.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, type IIA mostly contains isolates from Europe (Bergua et al. ). Our phylogenetic relationship analysis using 21 AMV isolates (Table S1) is in accordance with previous genetic studies based on sequences of the CP gene (Parrella et al.…”
Section: Resultsmentioning
confidence: 99%